Repression without borders. The Movements for Amnesty Brazil and Europe (1960-1970) (Tempo e Argumento, 2023)
During the 1970s, the European Amnesty Committees were a recurring theme of the Brazilian Military Dictatorship's information agencies, the Information Community. On the outside, the agencies that were notable for establishing the surveillance system were the Foreign Information Center (CIEX) and the Sectoral Information Division of the Ministry of Foreign Affairs (DSI/MRE). For exiles, the connections promoted between Brazil and Europe collaborated in expanding the political guidelines of the Movements for Amnesty. In this context, the mobilizations for Amnesty served to broaden the transnational sound of the discourse on human rights, to include the serious violations committed by the military government in Brazil, aided by entities that raised the flag of human rights, such as Amnesty International and the Court Bertrand Russell II.
Keywords: brazilian military dictatorship; amnesty; Europe; information community; Therezinha Zerbine